Implementation of Inventory Management System on Baby Stuff Batam - Lena Sepriani; Candy Candy (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
This study aims to implement a website-based inventory management system using the EOQ and ROP methods to control the inventory of products owned by Baby Stuff Batam to obtain more profits and more effective operational performance. From the results of the interview with the business owner of Baby Stuff Batam, it is known that the owner often has difficulty managing the stock of products because of the large number of product stocks that are excess or lacking, and the business owner only relies on handwritten notes. The results of this study are the output generated in the inventory management system in the form of stock reports, purchase and sale transaction reports, and EOQ reports to find out the right amount and time to buy the products. After implementing a website-based inventory management system on Baby Stuff Batam, the results are quite positive and useful for increasing the effectiveness of partner business operational performance.